2016
DOI: 10.4055/cios.2016.8.4.373
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of a Novel Wedge Locking Plate in a Porcine Tibial Model

Abstract: BackgroundThe purpose of this study was to analyze biomechanical properties of a novel wedge locking plate in medial open wedge high tibial osteotomy (OWHTO) in a porcine tibial model.MethodsA uniform 8-mm OWHTO was performed in 12 porcine tibiae. Six of them were subsequently fixed with the plate without a wedge, whereas the other 6 were additionally reinforced with a metal wedge of 8 mm. Biomechanical properties (stiffness, displacement of the osteotomy gap, and failure load) were evaluated under axial load.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Therefore, CT is a more accurate method for detecting hinge fractures and will be useful for deciding the postoperative rehabilitation protocol after corrective osteotomy around the knee. In contrast to studies on high tibial osteotomy, 7,8,11,22 a few clinical studies investigated the factors that affect bone healing after distal femoral osteotomy. A recent clinical study demonstrated that a biplanar osteotomy technique shortens the bone healing time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, CT is a more accurate method for detecting hinge fractures and will be useful for deciding the postoperative rehabilitation protocol after corrective osteotomy around the knee. In contrast to studies on high tibial osteotomy, 7,8,11,22 a few clinical studies investigated the factors that affect bone healing after distal femoral osteotomy. A recent clinical study demonstrated that a biplanar osteotomy technique shortens the bone healing time.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to studies on high tibial osteotomy, 7,8,11,22 a few clinical studies investigated the factors that affect bone healing after distal femoral osteotomy. A recent clinical study demonstrated that a biplanar osteotomy technique shortens the bone healing time.…”
Section: Discussionmentioning
confidence: 99%
“…High tibial osteotomy (HTO) is an effective treatment method to manage young patients with varus deformity paired with osteoarthritis (OA) of the medial compartment. [1][2][3] In this context, the weight-bearing axis can be shifted laterally after surgery and, as a result, the unloading of the medial compartment could mitigate the medial OA. [4][5][6] However, valgus alignment after HTO reversely increases the loading of the lateral compartment, potentially provoking the degeneration of the lateral compartment to progress.…”
Section: Introductionmentioning
confidence: 99%
“…To maintain the corrected alignment after HTO, the use of locking plate and screws helps to establish a strong support for the osteotomied tibia till bone union [79]. In current practice of HTO, traditional titanium locking plate and screw fixation yields acceptable outcomes, and approximately 90% of the patients who returned to work or sport did so within 1 year [6].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain better results, further studies focused either on the structural stability established between the bone and plate or on the creation of beneficial biomechanical stimuli from interfragmentary movement via flexible/dynamic fixation were made in the past [1113]. In these biomechanical studies, some issues including the geometry and configuration of plate, the use of wedge spacer, and even the interfragmentary movement promoting callus formation during bony healing [7, 11, 1416] were investigated. However, to our note, a more fundamental factor, the screw, was less mentioned and rarely investigated.…”
Section: Introductionmentioning
confidence: 99%